ANALISIS PERILAKU K3 DALAM PENGOPERASIAN ALAT BERAT PT. TAMORA CIPTA UTAMA - Rizki, Zoel Alfa; Abizar, Haris (Ivet University, 2024)
The construction industry occupies the top position as a whole when viewed at the incidence rate of work accidents. This study aims to understand more deeply the factors that cause work accidents in the Bandung people's struggle monument (continued) area arrangement project, especially for heavy equipment operation. This research uses qualitative research as a type of research. Quality research emphasizes obtaining more in-depth data, especially involving researchers directly in the field. Based on the results of the study, the level of awareness of workers on knowledge are: K3 Principle 33%, Danger and Risk 50%, K3 Regulation 17% and Application of K3, namely: Use of PPE 0%, Safety Check 67%, Following Evacuation Procedures 33%.